Сайтобудування. тематичний сайт-техблог про інженерію і науку - Ткаченко, М. А. (ХНУРЕ, 2022)
This thematic techblog that is dedicated to engineering and science. Engineering is the use of science to design and build projects that solve people's problems. Why you should become an engineer. The whole world around was designed by engineers. You use fruits of engineering in everyday life. Engineering is a collaborative field. As we know nothing great is made alone. Together, engineers are capable of creating great megaprojects. Engineers are high-paid, in demand, and a wide range of specialties for all interests from Earth infrastructure to space. Engineering is based upon science. Modern science was "plugged into" 450 years ago. It happened recently in the history of mankind. And people have already achieved incredible results.